The association between authoritarian parenting style and peer interactions among Chinese children aged 3–6: an analysis of heterogeneity effects - Li, Dexian; Li, Wencan; Zhu, Xingchen (Frontiers in Psychology, 2024)
This study explores the effects of authoritarian parenting styles on children's peer interactions, an aspect often overlooked in the existing literature that primarily focuses on family environmental factors. Data was collected through anonymous child-report questionnaires completed by 2303 parents and teachers of children aged 3-6 years. The findings reveal that (1) authoritarian parenting significantly hinders children's peer interactions; (2) the negative effects of authoritarian parenting differ based on gender, age, and family composition: (a) girls generally exhibit higher peer interactions than boys, with authoritarian parenting having a stronger impact on boys' peer interactions; (b) peer interactions increase significantly with age, and younger children are more susceptible to the negative effects of authoritarian parenting; (c) children with siblings have higher peer interactions, and authoritarian parenting style has a greater influence on their interactions compared to only children. The study discusses potential reasons and provides practical suggestions for families to make informed parenting style choices based on these findings.